Mechanically induced oxidation of alcohols to aldehydes and ketones in ambient air: Revisiting TEMPO-assisted oxidations - Porcheddu, Andrea; Colacino, Evelina; Cravotto, Giancarlo; Delogu, Francesco; De Luca, Lidia (Beilstein Journal of Organic Chemistry, 2017)
The present work addresses the development of an eco-friendly and cost-efficient protocol for the oxidation of primary and secondary alcohols to the corresponding aldehydes and ketones by mechanical processing under air. Ball milling was shown to promote the quantitative conversion of a broad set of alcohols into carbonyl compounds with no trace of an over-oxidation to carboxylic acids. The mechanochemical reaction exhibited higher yields and rates than the classical, homogeneous, TEMPO-based oxidation.
Keywords: aldehydes; ball milling; ketones; mechanochemistry; oxidation reactions; TEMPO

Comprehensive Organic Transformations: A Guide to Functional Group Preparations - Dubrovskiy, A. V.; Kesharwani, T.; Markina, N. A.; Pletnev, A. A.; Raminelli, C.; Yao, T.; Zeni, G.; Zhang, L.; Zhang, X.; Rozhkov, R.; Larock, R. C. (Wiley, 2017)

March's Advanced Organic Chemistry: Reactions, Mechanisms, and Structure - Smith, B. H. (John Wiley & Sons, 2013)

Classics in Total Synthesis: Targets, Strategies, Methods - Nicolaou, K. C.; Sorensen, E. J. (Wiley-VCH, 1996)

Chemistry of the Carbonyl Group: A Programmed Approach to Organic Reaction Mechanism - Warren, S. (John Wiley & Sons, 1974)

Oxidations of Alcohols to Aldehydes and Ketones -A Guide to Current Common Practice - Tojo, G.; Fernandez, M. (Springer, 2006)

Oxidations in Organic Chemistry - Hudlucky, M. (American Chemical Society, 1990)

(untitled) - Mancuso, A. J.; Huang, S.-L.; Swern, D. (J. Org. Chem., 1978)

(untitled) - Dess, D. B.; Martin, J. C. (J. Org. Chem., 1983)

(untitled) - Ley, S. V.; Norman, J.; Griffith, W. P.; Marsden, S. P. (Synthesis, 1994)

(untitled) - Baxendale, I. R.; Deeley, J.; Griffiths-Jones, C. M.; Ley, S. V.; Saaby, S.; Tranmer, G. K. (Chem. Commun., 2006)

Modern Oxidation Methods - Arends, I. W. C. E.; Sheldon, R. A.; Bäckvall, J. E. (Wiley-VCH, 2011)

(untitled) - Boisvert, L.; Goldberg, K. I. (Acc. Chem. Res., 2012)

(untitled) - Luzzio, F. A.; Guziec, F. S., Jr (Org. Prep. Proced. Int., 1988)

(untitled) - Fatiadi, A. J. (Synthesis, 1976)

(untitled) - Tidwell, T. T. (Synthesis, 1990)

(untitled) - Sheldon, R. A.; Arends, I. W. C. E.; ten Brink, G.-J.; Dijksman, A. (Acc. Chem. Res., 2002)

(untitled) - Tohma, H.; Kita, Y. (Adv. Synth. Catal., 2004)

(untitled) - Cella, J. A.; Kelley, J. A.; Kenehan, E. F. (J. Org. Chem., 1975)

(untitled) - Ganem, B. (J. Org. Chem., 1975)

(untitled) - Anelli, P. L.; Biffi, C.; Montanari, F.; Quici, S. (J. Org. Chem., 1987)

(untitled) - De Luca, L.; Giacomelli, G.; Porcheddu, A. (Org. Lett., 2001)

(untitled) - Bolm, C.; Magnus, A. S.; Hildebrand, J. P. (Org. Lett., 2000)

(untitled) - Markó, I. E.; Giles, P. R.; Tsukazaki, M.; Brown, S. M.; Urch, C. J. (Science, 1996)

(untitled) - Hoover, J. M.; Steves, J. E.; Stahl, S. S. (Nat. Protoc., 2012)

(untitled) - Hoover, J. M.; Ryland, B. L.; Stahl, S. S. (J. Am. Chem. Soc., 2013)

(untitled) - Könning, D.; Olbrisch, T.; Sypaseuth, F. D.; Tzschucke, C. C.; Christmann, M. (Chem. Commun., 2014)

(untitled) - Ryland, B. L.; Stahl, S. S. (Angew. Chem., Int. Ed., 2014)
and references cited therein.

(untitled) - Allen, S. E.; Walvoord, R. R.; Padilla-Salinas, R.; Kozlowski, M. C. (Chem. Rev., 2013)

(untitled) - Wang, L.; Shang, S. S.; Li, G.; Ren, L.; Lv, Y.; Gao, S. (J. Org. Chem., 2016)

(untitled) - Ma, S.; Liu, J.; Li, S.; Chen, B.; Cheng, J.; Kuang, J.; Liu, Y.; Wan, B.; Wang, Y.; Ye, Y.; Yu, Q.; Yuan, W.; et al. (Adv. Synth. Catal., 2011)

(untitled) - Alfonsi, K.; Colberg, J.; Dunn, P. J.; Fevig, T.; Jennings, S.; Johnson, T. A.; Kleine, H. P.; Knight, C.; Nagy, M. A.; Perry, D. A.; Stefaniak, M. (Green Chem., 2008)

(untitled) - Cao, Q.; Dornan, L. M.; Rogan, L.; Hughes, N. L.; Muldoon, M. J. (Chem. Commun., 2014)

(untitled) - Sheldon, R. A. (Chem. Soc. Rev., 2012)
Acetonitrile is considered by the US Environmental Protection Agency as a hazardous solvent that produces acute systemic and potentially carcinogenic effects.

(untitled) - Trost, B. M. (Science, 1991)

(untitled) - Parmeggiani, C.; Cardona, F. (Green Chem., 2012)

(untitled) - Rothenberg, G.; Downie, A. P.; Raston, C. L.; Scott, J. L. (J. Am. Chem. Soc., 2001)

(untitled) - Hernández, J. G.; Juaristi, E. (J. Org. Chem., 2010)

(untitled) - Tabasso, S.; Carnaroglio, D.; Calcio Gaudino, E.; Cravotto, G. (Green Chem., 2015)

Mechanochemistry: From Functional Solids to Single Molecule - Eagling, R. (Royal Society of Chemistry, 2014)

(untitled) - Humphry-Baker, S. A.; Garroni, S.; Delogu, F.; Schuh, C. A. (Nat. Mater., 2016)

Ball Milling Towards Green Synthesis: Applications, Projects, Challenges - Cravotto, G.; Calcio Gaudino, E. (Oxidation and reduction by solid oxidants and reducing agents using ball milling, 2014)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

Mechanochemical Organic Synthesis - Margetic, D.; Štrukil, V. (Elselvier, 2016)

(untitled) - Friščić, T.; Childs, S. L.; Rizvi, S. A. A.; Jones, W. (CrystEngComm, 2009)

(untitled) - Hasa, D.; Miniussi, E.; Jones, W. (Cryst. Growth Des., 2016)

(untitled) - Rodriguez, B.; Bruckmann, A.; Rantanen, T.; Bolm, C. (Adv. Synth. Catal., 2007)

(untitled) - Stolle, A.; Szuppa, T.; Leonhardt, S. E. S.; Ondruschka, B. (Chem. Soc. Rev., 2011)

(untitled) - Tan, D.; Loots, L.; Friščić, T. (Chem. Commun., 2016)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Cravotto, G.; Garella, D.; Carnaroglio, D.; Calcio Gaudino, E.; Rosati, O. (Chem. Commun., 2012)

Ball Milling Towards Green Synthesis: Applications, Projects, Challenges - Stolle, A.; Ranu, B. (The Royal Society of Chemistry, 2015)

(untitled) - Hernández, J. G.; Friščić, T. (Tetrahedron Lett., 2015)

Ball Milling Towards Green Synthesis: Applications, Projects, Challenges - Machuca, E.; Juaristi, E.; Brindaban, R.; Stolle, A. (Asymmetric Organocatalytic Reactions Under Ball Milling, 2015)

(untitled) - Hernández, J. G.; Frings, M.; Bolm, C. (ChemCatChem, 2016)

(untitled) - Mocci, R.; De Luca, L.; Delogu, F.; Porcheddu, A. (Adv. Synth. Catal., 2016)

(untitled) - Gaspa, S.; Porcheddu, A.; Valentoni, A.; Garroni, S.; Enzo, S.; De Luca, L. (Eur. J. Org. Chem., 2017)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

(untitled) - Do, J.-L.; Friščić, T. (ACS Cent. Sci., 2017)

(untitled) - Takacs, L. (Chem. Soc. Rev., 2013)

(untitled) - Boldyreva, E. (Chem. Soc. Rev., 2013)

(untitled) - Baláž, P.; Achimovičová, M.; Baláž, M.; Billik, P.; Cherkezova-Zheleva, Z.; Criado, J. M.; Delogu, F.; Dutková, E.; Gaffet, E.; Gotor, F. J.; Kumar, R.; Mitov, I.; et al. (Chem. Soc. Rev., 2013)

(untitled) - Friščić, T.; Jones, W. (Cryst. Growth Des., 2009)

(untitled) - Friščić, T. (Chem. Soc. Rev., 2012)

(untitled) - Sahoo, P. K.; Bose, A.; Mal, P. (Eur. J. Org. Chem., 2015)
In 2015, Mal et al. reported the first example of a very interesting solvent free ball-milling oxidation of activated primary alcohols to aldehyde using NBS (1.5 equiv) or oxone (0.6 equiv) as co-oxidising agents. This paper has laid the foundation for further studies on this topic.

(untitled) - Rightmire, N. R.; Hanusa, T. P. (Dalton Trans., 2016)
The formalism for mechanochemically activated reactions was proposed here.

(untitled) - Lanzillotto, M.; Konnert, L.; Lamaty, F.; Martinez, J.; Colacino, E. (ACS Sustainable Chem. Eng., 2015)

(untitled) - Konnert, L.; Lamaty, F.; Martinez, J.; Colacino, E. (J. Org. Chem., 2014)

(untitled) - Konnert, L.; Gauliard, A.; Lamaty, F.; Martinez, J.; Colacino, E. (ACS Sustainable Chem. Eng., 2013)

(untitled) - Rogan, L.; Hughes, N. L.; Cao, Q.; Dornan, L. M.; Muldoon, M. J. (Catal. Sci. Technol., 2014)